2008
DOI: 10.1111/j.1439-0310.2007.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bold and the Variable: Fish with High Heterozygosity Act Recklessly in the Vicinity of Predators

Abstract: Variation in the innate behavioral response to predation threat is often assumed to reflect genetic differences among the prey individuals. To date, no published results, however, exist that would offer explanation for the origin of this behavioral variation within populations. Using microsatellites as markers, we estimated the genetic variability of juvenile brown trout (Salmo trutta) individuals whose behavior had been individually recorded in a trade‐off situation where both predator chemical cues and food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
0
18
1
Order By: Relevance
“…Genetic variation has previously been shown to correlate with various measures of fitness (David 1998;Wang et al 2002) and influences individual behaviour (Tiira et al 2003;Vilhunen et al 2008). Susceptibility to toxicant pollution has also been shown to be significantly affected by genetic S TE TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TE TE TE TE TE TE TE TE TE TE TE TE TE TE TE AB variability; reduced levels being correlated with a lower tolerance to pollutants (Nowak et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variation has previously been shown to correlate with various measures of fitness (David 1998;Wang et al 2002) and influences individual behaviour (Tiira et al 2003;Vilhunen et al 2008). Susceptibility to toxicant pollution has also been shown to be significantly affected by genetic S TE TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TL TE TE TE TE TE TE TE TE TE TE TE TE TE TE TE AB variability; reduced levels being correlated with a lower tolerance to pollutants (Nowak et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For example, for some non‐mammalian species, it has been observed that personality differences with regard to boldness in exploring novel habitats may affect dispersal (Dingemanse et al. 2003), and boldness can be related to genetic diversity (Vilhunen et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the exploration distance was not directly linked to heterozygosity either, but through some covariate trait. For example, for some non-mammalian species, it has been observed that personality differences with regard to boldness in exploring novel habitats may affect dispersal (Dingemanse et al 2003), and boldness can be related to genetic diversity (Vilhunen et al 2008). Risk-taking related behaviour is also linked to dispersal in American red squirrels, Tamiasciurus hudsonicus (Boon, Re´ale & Boutin 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of predators may have evolutionary consequences (Portz and Harold, 2004;Walsh and Reznick, 2008;Smirnova and Gerasimov, 2010). Individual behavior plays an important role in the success of defensive activity (Lister and Neff, 2006;Vilhunen et al, 2008). Populations include the specimens able for more effi cient foraging in the presence of a predator minimiz ing at the same time the risk to be eaten.…”
Section: Biotopic Segregation and Trophic Polymorphism In The Populatmentioning
confidence: 99%